The relation between interleukin-31 serum levels and Staphylococcus aureus skin colonization in pediatric atopic dermatitis. Issue 1 (January 2015) - Ismail, Eisha A.; Ibrahim, Hala A.; Farid, Carmen I.; Okasha, Hadir A.; Soliman, Eman A.
<x xml:space="preserve">Abstract</x> Background Pruritus is a distressing symptom in atopic dermatitis (AD). Interleukin-31 (IL-31) has lately been a focus of research for its relation with severity of both dermatitis and pruritus. Staphylococcus aureus enterotoxins were suggested to induce its expression and hence augment pruritus in AD patients. Objective To verify the relation between serum IL-31 level, S. aureus skin colonization, and the development and severity of AD in children. Patients and methods In the present case–control study, a total of 30 AD children of different severities were included and 30 healthy age and sex matched individuals served as controls. SCORAD score was calculated for all patients. The serum level of IL-31 as well as S. aureus skin colonization density were determined for patients before and after receiving treatment for their condition, as well as for controls. Statistical analysis of the data was then carried out. Results A significant association was found between IL-31 serum levels and AD (P<0.001), but it did not correlate with disease severity nor with pruritus intensity. S. aureus colonization density correlated positively with disease severity (P=0.004 and 0.03 before and after treatment, respectively) and pruritus intensity (P=0.004 and 0.03 before and after treatment, respectively), but it did not correlate with serum levels of IL-31. Conclusion IL-31 may be important in the pathophysiology of AD but is not a marker of disease severity or pruritus. S. aureus colonization density is reflected through disease severity and is associated with pruritus with no relation to IL-31.